Penerapan Konsep Bangunan Hijau dalam kalangan Penghuni Kolej Kediaman di Universiti Tun Hussein Onn Malaysia - Ayob, Aina Farhana; OMAR, ROSHARTINI; Goh Kai Chen; Seow Ta Wee (Research in Management of Technology and Business, 2025)
There is still a lack of knowledge and acceptance of green initiatives in residential colleges at University Tun Hussein Onn Malaysia (UTHM), as seen by the residents’ limited use of green building principles. This research looks at many important problems that impede efforts towards sustainable development when it comes to the use of green construction ideas by the inhabitants of UTHM’s residential colleges, such as high upfront expenses, a lack of knowledge, and inadequate institutional support. With the use of renewable energy and effective resource management, the study’s primary goal is to create a more pleasant and healthy atmosphere that will promote students’ well-being and lessen its impact on the environment. Thus, this study’s goals are to pinpoint the primary issues with green building implementation in residential colleges and suggest solutions to enhance it. A 64.2% response rate was obtained from the survey, which had 219 respondents out of 341 inhabitants from Kolej Tun Fatimah and Kolej Tun Dr. Ismail. SPSS version 27 was used for both descriptive and inferential analysis of the data gathered via structured questionnaires. Three primary problems were identified by the analysis’s findings: inadequate institutional support, high beginning expenses (65%), and ignorance (60%). Among the suggested measures to address these issues are awareness campaigns (70%), improved infrastructure support (60%), and direct student involvement in green building programs (55%). The implementation of these measures is expected to improve students’ quality of life through better indoor air quality, reduced pollution and health issues, and help the university achieve its sustainable development goals through energy efficiency and the sustainability of the residential colleges.